Comparison Of Legal Protection Of Labor Wages In Indonesia And Singapore - muliawan, chandra; Tilalinata, Aifi; Charda, Flora Nita; Sari, Evi Meiriza (Universitas Malayati, 2024)
The lack of job vacancies in Indonesia has resulted in many citizens preferring to go abroad such as Singapore to look for work, they work as Indonesian workers (TKI) . The aim of this research is to find out legal protection for Indonesian workers. In this research the author uses normative juridical legal research methods or library research. The results of the research show that regarding the protection of workers' wages, Indonesia has regulated it clearly in Law Number 13 of 2003 concerning Employment and Government Regulation of the Republic of Indonesia No. 3 of 2013 concerning Protection of Indonesian Workers Abroad. The Role of the Government in Indonesia in Protecting Indonesian Workers (TKI) in Singapore are regulated in Law no . 39 of 2004 and supported by Law No. 37 of 1999 concerning Foreign Relations . The Indonesian government has taken steps to protect Indonesian migrant workers, including through the enactment and ratification of Law Number 39 of 2004 concerning the Detention and Protection of Indonesian Migrant Workers Abroad , the Establishment of the National Agency for the Placement and Protection of Indonesian Migrant Workers (BPN2TKI)Keywords : Indonesian Workers, Legal Protection, International Law